Evaluation of Human Leukocyte Antigen Class I and Class II in End-Stage Renal Disease Occurrence in Indonesian Transplantation Patients - Hani Susianti; Dwi Priyadi Djatmiko; I Komang Adi Widana; Deasy Ayuningtyas Tandio; Catur Suci Sutrisnani; Singgih Pudjo Wahono; Ira Puspitawati (International Journal of Nephrology)
Background. Genetic studies of end-stage renal disease (ESRD), including those of human leukocyte antigen (HLA) genes, have been reported in several populations but have not yet been evaluated in Indonesia. Some studies have reported that these genes had a substantial role in ESRD. This study aims to analyze the association between HLA genes and ESRD within the Indonesian community. Method. A retrospective study to investigate HLA class I and II alleles to find out the distribution of HLA-A, -B, -C, -DPB1, -DQB1, and -DRB1 in renal transplant recipients and to ascertain their role in susceptibility to ESRD was performed on totally 149 subjects, consisting of 69 ESRD patients and 80 healthy controls. HLA typing was determined using Luminex techniques. The allele and haplotype frequencies were compared between ESRD patients and controls. Result. High-frequency alleles were HLA-A∗24 (43.6%), B∗15 (38.2%), C∗08 (30.8%), DRB1∗12 (47.3%), DQB1∗03 (50.6%), and DPB1∗13 (22.5%). HLA-A∗24 p=0.01 and HLA-B∗35 p=0.02 were associated with a protective effect, with OR 0.537 (95%CI 0.34–0.86) and 0.316 (95%CI 0.11–0.88), respectively. There were some two-locus haplotypes associated with susceptibility to ESRD, such as B∗15-DRB1∗12, B∗13-DRB1∗15, A∗02-B∗15, A∗02-C∗08, and B∗13-DQB1∗05. HLA-A∗02-B∗15-DRB1∗12 and A∗24-B∗13-DRB1∗15 appear to be associated with susceptibility to ESRD. Conclusion. The allele groups of HLA-A∗24 and HLA-B∗35 are associated with protection from ESRD. Meanwhile, HLA-B∗13-DRB1∗15 and A∗24-B∗13-DRB1∗15 are the most frequent HLAs associated with ESRD in two-locus and three-locus haplotype, respectively.